Spontanous Vulvar Endometriosis: Report of A Case - Coşkun Ümit; Mahmut Kuntay Kokanalı; Selçuk Erkılınç; Melike Doğanay (Medical Network, 2016)
Endometriosis is an ectopic occurrence of tissue morphologically and functionally resembling endometrial tissue outside the uterine cavity. Vulva is one of the rarest location of extrapelvic endometriozis. We report a case of a 44-year-old multiparous woman, referred to our clinic with the complaints of having a vulvar mass and cyclic swelling of the mass during menstruation. She had a history of 2 previous cesarean delivery and no history of previous vulvar or vaginal surgery. The mass was 3-4cm in diameter and localized on the upper-portion of the right labium minus. Complete surgical excision was performed with the suspicion of endometriosis. Final histopathology report confirmed the diagnosis of endometriosis. Three weeks after surgery there was no evidence of endometriosis. In conclusion whether or not having a history of a previous vulvar surgery, vulvar endometriosis should be considered as a part of differential diagnosis in evaluation of vulvar masses.